The effect of hypomagnetic field on survival and mitochondrial functionality of active Paramacrobiotus experimentalis females and males of different age - Nagwani, Amit Kumar; Budka, Anna; Łacka, Agnieszka; Kaczmarek, Łukasz; Kmita, Hanna (Frontiers in Physiology, 2023)
Even for tardigrades, often called the toughest animals on Earth, a hypomagnetic field (HMF) is an extreme environment. However, studies on the effect of HMF on tardigrades and other invertebrates are scarce. Mitochondria play an important role in an organism's response to extreme conditions. The effect of HMF on the mitochondrial inner membrane potential (Δψ), a well-known marker of mitochondria functionality, shows that mitochondria are very sensitive to HMF. To measure the HMF effect on Paramacrobiotus experimentalis, we calculated the tardigrade survival rate and Δψ level after HMF treatments of different durations. We also estimated the relationship between the age and sex of the tardigrade and the HMF effect. We observed age-and sex-related differences in ψ and found that ψ changes after HMF treatment were dependent on its duration as well as the animal's age and sex. Furthermore, active P. experimentalis individuals displayed a high survival rate after HMF treatment. The data may contribute to the understanding of tardigrade aging and their resistance to extreme conditions including HMF, which in turn may be useful for future space explorations.